2007
DOI: 10.1007/s00705-007-0954-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-seasonal diversity of norovirus genotypes: Emergence and selection of virus variants

Abstract: This study describes a method used to determine the diversity of NoVs co-circulating in the community that consisted of the analysis of a limited number of strains collected from outbreaks occurring at different times of the NoV season. The diversity of twenty NoV strains collected from outbreaks occurring at the beginning of each NoV season (September) was compared to the diversity found in the middle (December) and at the end of the season (March). The method was validated through the characterisation of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 28 publications
6
87
0
1
Order By: Relevance
“…Second, it has been suggested that the at Library on April 12, 2010 http://aje.oxfordjournals.org marked winter-time increase in hospital admissions for respiratory infections may drive the strong seasonality of norovirus outbreaks in this setting, and that there are distinct norovirus strains circulating in hospital populations and in the community that may have different transmission characteristics (29); therefore, the incidence of community disease or general practitioner consultations would not necessarily show the marked seasonality seen in health careassociated outbreaks. However, detailed characterization of the molecular epidemiology of norovirus infections in the community is needed, for comparison with the extensive data that already exist for hospital-acquired infections (30,31), to understand better the factors driving the different seasonality of health-care outbreaks and community disease. Finally, it is also possible that there was more outof-season norovirus transmission during this study because of the emergence of a new norovirus variant, as described above (32).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been suggested that the at Library on April 12, 2010 http://aje.oxfordjournals.org marked winter-time increase in hospital admissions for respiratory infections may drive the strong seasonality of norovirus outbreaks in this setting, and that there are distinct norovirus strains circulating in hospital populations and in the community that may have different transmission characteristics (29); therefore, the incidence of community disease or general practitioner consultations would not necessarily show the marked seasonality seen in health careassociated outbreaks. However, detailed characterization of the molecular epidemiology of norovirus infections in the community is needed, for comparison with the extensive data that already exist for hospital-acquired infections (30,31), to understand better the factors driving the different seasonality of health-care outbreaks and community disease. Finally, it is also possible that there was more outof-season norovirus transmission during this study because of the emergence of a new norovirus variant, as described above (32).…”
Section: Discussionmentioning
confidence: 99%
“…Small batches of fecal specimens were prepared as described previously using the guanidinium thiocyanate-silica method (10) or in larger batches using a Roche total nucleic acid extraction kit (Roche Diagnostics Ltd., Burgess Hill, United Kingdom) according to manufacturer's instructions and a Roche MagNAPure automated extractor (7). Briefly, for the guanidinium thiocyanate-silica procedure, a 200-ul fecal extract in phosphate-buffered saline was added to 1 ml of L6 buffer (Severn Biotech, United Kingdom) and 20 l of silica, and the silica pellet was then washed with L2 buffer (Severn Biotech, United Kingdom)-70% ethanol-acetone.…”
Section: Fecalmentioning
confidence: 99%
“…Different genome fragments, such as region A (part of the RdRp gene), region C (part of the capsid gene), or the region spanning the ORF1 and ORF2, have been used to demonstrate the evolution of GII.4 variants [Gallimore et al, 2007;Siebenga et al, 2007b;Buesa et al, 2008]. In this study, sequence analysis of the region A allowed us to demonstrate that three GII.4 variants, 2004GII.4 variants, , 2006aGII.4 variants, , and 2006b phylogenetic tree confirming their close evolutionary relationships [Siebenga et al, 2007b;Buesa et al, 2008] [Gallimore et al, 2007;Buesa et al, 2008;Reuter et al, 2008;Siebenga et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…ORF2 sequences representative of the six GII.4 variants recovered in Europe in the last 15 years. The characteristic motifs reported by Gallimore et al [2007], based on the amino acids at position 6, 9, and 15, were taken into consideration for determination of the variant. This allowed the identification of four NoV variants, 2002NoV variants, , 2004NoV variants, , 2006aNoV variants, , and 2006b, in agreement with the results obtained by RdRp sequence analysis (Fig.…”
Section: Genetic Analysis Of Gii4 Novsmentioning
confidence: 99%
See 1 more Smart Citation